(untitled) (Prosiding dan Call Paper Widya Wiwaha, 2023)
The main problem in this study is due to the gaps and phenomena between product purchase transactions in general where online transactions are more attractive to consumers. This study aims to analyze the effect of online sales and consumer satisfaction on purchasing decisions at the Mutiara Cosmetic Center in Yogyakarta City. The type of method used in this research is quantitative methods using SPSS version 2.2. Data collection techniques in this study used a questionnaire measured by a Likert scale. The samples used were 47 respondents who were consumers at the Mutiara Cosmetic Center in Yogyakarta City. The analytical method used is instrument test, classical assumption test, multiple linear regression test, hypothesis test and determination coefficient. The results of this study indicate that simultaneously the independent variables of online sales and customer satisfaction have a significant effect on the dependent variable, namely purchasing decisions. Partially, it can be seen the t-test results which show that the online sales variable has a significance level of 0.004 less than0.05. While the consumer satisfaction variable has a significant level of 0.001 less than0.05. Based on these calculations, it can be concluded that partially online sales and customer satisfaction have a significant effect on purchasing decisions.